Realization of a flat-response photocathode for x-ray streak cameras - Wang, Chuanke; Li, Jin; Hu, Xin; Hu, Zhimin; Zhu, Xiaoli; Deng, Bo; Yi, Tao; Fan, Quanping; Cao, Zhurong; Liu, Shenye; Jiang, Shaoen; Ding, Yongkun; et al. (Optics express, 2015)
We present a novel photocathode which can make x-ray streak cameras to be of a flat spectral response in the x-ray energy range of 0.1-5 keV. The photocathode consists of two layers of gold foils with optimized thickness ratio and structures. The photocathode was calibrated, and it is shown that a flat spectral response has been achieved.